IKAN CAPUNGAN BANGGAI (Pterapogon kauderni) DAN UPAYA UNTUK MENDAFTARKAN SPESIES INI DALAM APPENDIX II CITES - Ani Mardiastuti; Soehartono, Tonny R. (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Banggai cardinalfish (Pterapogon kauderni) is a commercial ornamental fish originated and endemic to Banggai Islands of Indonesia. The objective of this paper was (a) to examine the sequence and the reasons to include Banggai cardinalfish into CITES Appendix II by USA and again by European Union, (b) to explain the responds (policy and actions) by Indonesian Government, and (c) to analyse the impact of the international and national policies related to CITES decisions. Basically, USA and EU claimed that the exploitation of Banggai cardinalfish for export was over-harvested and unsustainable, and thus they proposed to include the species into CITES Appendix II. The Government of Indonesia considered that the species has been appropriately managed in accordance to sustainable yield, and thus this species no need to include in the CITES Appendix II. To ensure its sustainability, the Government has issued a number of activities and interventions, among other, imposing limited access to harvest area, establishment of breeding operations, study of its natural population as well as development of a national action plan. After a long process involving various institutions, Bangai cardinalfish was decided not to be included in CITES Appendix II. Conservation measures, however, need to be continued by Indonesian Government to make sure that the population and the trade of Banggai cardinalfish will be sustainable in the future.